The Role of Leaflets as a Means of Reproductive Health Education for Adolescents at Trisakti Private Middle School, Lubuk Pakam - Raisha Octavariny; Sri Melda Br Bangun; Wilda Wahyuni Siregar; Helni W.L Simarmata (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Adolescents are in a critical stage of growth and development, making reproductive health education essential. This study aimed to analyze the role of leaflet media as an educational tool in improving adolescents' knowledge about reproductive health at SMP Swasta Trisakti Lubuk Pakam. The research used a quantitative design with a pre-test and post-test approach involving 41 respondents selected purposively. Data were collected using questionnaires before and after the health promotion intervention. Analysis was conducted with paired sample t-test. The results show a significant increase in knowledge after leaflet distribution, with respondents in the good knowledge category increasing from 56.1% to 78.0%. The statistical test yielded a p-value = 0.001 (p < 0.05), indicating a significant effect. It can be concluded that leaflet media is effective as an educational tool to increase adolescent reproductive health knowledge, and it can be recommended as a school-based health promotion strategy.